Further delineation of the female phenotype with KDM5C disease causing variants: 19 new individuals and review of the literature. Issue 1 (29th May 2020) - Carmignac, Virginie; Nambot, Sophie; Lehalle, Daphné; Callier, Patrick; Moortgat, Stephanie; Benoit, Valérie; Ghoumid, Jamal; Delobel, Bruno; Smol, Thomas; Thuillier, Caroline; Zordan, Cécile; Naudion, Sophie; et al.
Abstract: X‐linked intellectual disability (XLID) is a genetically heterogeneous condition involving more than 100 genes. To date, 35 pathogenic variants have been reported in the lysine specific demethylase 5C ( KDM5C ) gene. KDM5C variants are one of the major causes of moderate to severe XLID. Affected males present with short stature, distinctive facial features, behavioral disorders, epilepsy, and spasticity. For most of these variants, related female carriers have been reported, but phenotypic descriptions were poor. Here, we present clinical and molecular features of 19 females carrying 10 novel heterozygous variants affecting KDM5C function, including five probands with de novo variants. Four heterozygous females were asymptomatic. All affected individuals presented with learning disabilities or ID (mostly moderate), and four also had a language impairment mainly affecting expression. Behavioral disturbances were frequent, and endocrine disorders were more frequent in females. In conclusion, our findings provide evidence of the role of KDM5C in ID in females highlighting the increasing implication of XLID genes in females, even in sporadic affected individuals. Disease expression of XLID in females should be taken into consideration for genetic counseling. Abstract : Graphical abstract summarizing clinical features of affected individuals carrying pathogenic variations of the KDM5C gene. Left: female with familial inheritance, Middle: females with de novo variations, Right: males.